Where's the evidence? debates in modern medicine - Silverman, William A. (Oxford : Oxford University Press, 1998)
New interventions in medicine have produced unexpected harmful effects. This text argues that comparisons must be made before new treatments are adopted to reduce the number of patients exposed to the unknown hazards of medical innovations.
Originally published: 1998.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Medical ethics; Evidence-based medicine; Perinatology -- Moral and ethical aspects